2011
DOI: 10.1021/ac202386w
|View full text |Cite
|
Sign up to set email alerts
|

Accelerated High-Resolution Differential Ion Mobility Separations Using Hydrogen

Abstract: The resolving power of differential ion mobility spectrometry (FAIMS) was dramatically increased recently by carrier gases comprising up to 75% He or various vapors, enabling many new applications. However, the need for resolution of complex mixtures is virtually open-ended and many topical analyses demand yet finer separations. Also, the resolving power gains are often at the expense of speed, in particular making high-resolution FAIMS incompatible with online liquid-phase separations. Here, we report FAIMS e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
121
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(126 citation statements)
references
References 57 publications
5
121
0
Order By: Relevance
“…21) As anticipated from simulations, separations in He/N 2 and H 2 /N 2 with equal N 2 fractions are similar, with slightly narrower peaks and thus higher resolution for the latter. 21) The main attraction, however, is stable operation at up to 85% H 2 , with the resolving power for larger 1+ ions improving by up to threefold as absolute compensation voltages or CVs (the FAIMS separation parameter) increase while peaks narrow further (Fig. 2).…”
supporting
confidence: 64%
See 2 more Smart Citations
“…21) As anticipated from simulations, separations in He/N 2 and H 2 /N 2 with equal N 2 fractions are similar, with slightly narrower peaks and thus higher resolution for the latter. 21) The main attraction, however, is stable operation at up to 85% H 2 , with the resolving power for larger 1+ ions improving by up to threefold as absolute compensation voltages or CVs (the FAIMS separation parameter) increase while peaks narrow further (Fig. 2).…”
supporting
confidence: 64%
“…21) As analytical methods mature, the resolution usually becomes limited more by the instrument parameter instabilities than physical factors. For example, the resolving power in modern time-of-flight MS is controlled mostly by the field uniformity, pusher voltage stability, and detector jitter rather than ion-ion Coulomb repulsion or other physical effects.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Shvartsburg et al . 133 have used hydrogen as dopant in a planar-FAIMS, obtaining an increase of the resolution up to 180 and exploring new applications as using them in hydrogen-rich media as in exoplanet atmospheres with dominant H 2 fractions (e.g., ∼87 and 96% for Jupiter and Saturn) 134, 135 . Puton et al .…”
Section: Effects Of Experimental Parametersmentioning
confidence: 99%
“…However, its resolving power was much lower than in conventional planar FAIMS due to the limited residence time in the short path length μFAIMS device. Several studies 2528 have shown that the performance of the μFAIMS can be enhanced when gases comprising helium 29 , hydrogen 30 or modifiers 31 are utilized. Thus, by enhancing the μFAIMS performance, new applications can potentially be extended into complex mixture studies and targeted analyses.…”
Section: Introductionmentioning
confidence: 99%